2014
DOI: 10.1111/vcp.12111
|View full text |Cite
|
Sign up to set email alerts
|

Stability of immunophenotypic lymphoid markers in fixed canine peripheral blood for flow cytometric analysis

Abstract: Background: Flow cytometric analysis of blood samples for immunophenotyping lymphoproliferative diseases has become popular in veterinary medicine. Unfortunately, the use of this technique has been limited by the necessity to test samples within a short time frame after blood collection. A possible solution to this problem is the use of fixative products to preserve the stability of lymphoid antigens. Objectives: The aim of this study was to evaluate the expression of 5 lymphoid surface markers (CD3, CD4, CD8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Although Streck Cell Preservative has not yet been validated for use in cats, it is routinely used by the authors for collection and shipment of feline and canine specimens for flow cytometric immunophenotyping. The authors' own experience shows that Streck Cell Preservative does not alter the expression of feline antigens or canine antigens …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Streck Cell Preservative has not yet been validated for use in cats, it is routinely used by the authors for collection and shipment of feline and canine specimens for flow cytometric immunophenotyping. The authors' own experience shows that Streck Cell Preservative does not alter the expression of feline antigens or canine antigens …”
Section: Discussionmentioning
confidence: 99%
“…The authors' own experience shows that Streck Cell Preservative does not alter the expression of feline antigens or canine antigens. 37 Authors' preliminary studies (data not shown) indicate that flow cytometric immunophenotyping is also useful in the diagnosis and characterization of non-FeLV-associated feline leukaemia, although further studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…All antibodies were from Serotec (Oxford, UK) except for anti‐TCRγδ provided by Leukocyte Antigen Biology Laboratory (UC Davis, CA, USA). Additional single color analysis for CD11d (clone CA11.8H2; AbD Serotec, Raleigh, North Carolina, USA) was performed at the Department of Veterinary Medicine, University of Cambridge with a FACSCalibur flow cytometer and CellQuest software (Becton‐Dickinson) . Overall, gated lymphoid cells were positive for CD3, CD5, CD45, and γδ‐TCR, and negative for the other antibodies tested (CD4, CD8, CD11d, CD21), confirming a γδ T‐cell origin.…”
Section: Case Presentationmentioning
confidence: 99%
“…Additionally, the loss of CD45 on T cells may have been secondary to delayed processing of the lymph node samples. A recent article showed that the expression of CD3 and CD45 decreased significantly starting 3 days after collection . Finally, it is possible that there was a continuum between the two disease processes.…”
Section: Discussionmentioning
confidence: 99%